Adaptasi Mahasiswa Dalam Mengatasi Culture Shock Dalam Perkuliahan - Enti Agestia; Desy Safitri; Sujarwo Sujarwo (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2024)
The shift from a high school environment to a college environment brings greater demands. This condition can cause the emergence of the culture shock phenomenon. This phenomenon underscores the importance of students having the ability to adapt to all demands that arise during lectures. Lecture adaptation refers to student interaction with the lecture environment. Considering the fact that lecture adaptation is complex, the forms of lecture adaptation are divided into 4 including academic adaptation, social adaptation, emotional adaptation, and adaptation to the institution. The purpose of this study is to find out more deeply about the adaptation carried out by students who experience culture shock in lectures. This research uses a qualitative method, to find out more about the adaptation carried out by students. The results of the study found that 1 in 4 students had not reached the adjusment stage, due to the complexity of adaptation to lectures. The three students who succeeded in adapting were none other than their efforts by being open to change, learning to develop themselves, and social support from dominant friends to help students adapt.